Effect of improving lumbar mobility, spinal stability ; with core stability training to achieve personal best runner - Zulhasniati Zulhasniati; Yudik Prasetyo; Nugroho Susanto; Andre Igoresky; Yogi Arnaldo Yogi Arnaldo; Gema Fitriady; Khoiril Anam; Zhanneta Kozina; Ratko Pavlovic; Ozgur Eken; Francesca Latino; Francesco Tafuri; et al. (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Running consists of simple basic movements, and to achieve these simple basic movements requires good mobility and stability, because the weakening of mobility and stability of the body causes misalignment or weakness of the legs so as to interfere with the absorption or propulsion phase in leg movement while running. Apply appropriate exercise methods to improve lumbar mobility and spinal stability. One training method that can be used is the core stability training method. Core stability is an exercise model to improve the ability to control the position of trunk movement through the pelvis and legs to allow optimal motion production. This study aims to ascertain whether core stability training can improve lumbar mobility and spinal stability in running athletes. The study used an experimental method with a research pattern using a group pretest-posttest design. 10 running athletes were sampled according to the criteria to be treated in the form of core stability training for 6 weeks. The athletes were assessed before and after training using the Functional Reach Test and Unilateral Hip Bridge Endurance. This study showed that there was a significant effect between core stability training and lumbar mobility (P = 0.000) and spinal stability (P = 0.000) in athletes. The results of this study show that the application of core stability exercises can increase the ability of lumbar mobility and spinal stability, so if the core stability exercises are done properly, they can increase stability in the spine and mobility in the lumbar, which causes dynamic limb movement to be more efficient.